MEMBINGKAI SPIRITUALITAS PENTAKOSTA DALAM PELAYANAN PASTORAL - Saputra, Rudyanto Chandra (Shift Key : Jurnal Teologi dan Pelayanan, 2022)
Pentecostal spirituality requires continuous reflection because it relates to the experience of the believer's spiritual life. The purpose of this research is to find out the understanding of God's servants about the implementation of the Pentecostal spirituality lifestyle in pastoral ministry, which includes leadership, worship, verbal words, gifts of the Holy Spirit, ministry and mission. This research method is quantitative research methods. The results of the study show a good level of understanding and suggest efforts to increase the understanding of the gifts of the Holy Spirit more significantly, complementing verbal pentecostalism and self-reliant ministry of the laity.